DAPA-HF trial: dapagliflozin evolves from a glucose-lowering agent to a therapy for heart failure - Edgardo Kaplinsky (BioExcel Publishing Ltd, 2020)
Heart failure (HF) continues to be a major global health problem with a notable impact in terms of morbidity and mortality and so, in consequence, with a large unmet necessity for new therapies. The inhibition of sodium-glucose cotransporter 2 (SGLT2) causes glycosuria and natriuresis, leading to reductions in hyperglycemia (antidiabetic effect), body weight, and blood pressure. In this context, outcome trials have been shown to reduce hospitalizations for HF in patients with type 2 diabetes mellitus treated with SGLT2 inhibitors. The underlying protective cardiovascular (CV) mechanisms of these agents are complex, multifactorial, and not entirely understood as, in addition to a diuretic-like function, SGLT2 inhibitors may mitigate glycemic-related toxicity, promote ketogenesis, increase hematocrit, and exert antihypertrophic, antifibrotic, and antiremodeling properties. The DAPA-HF (Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure) trial enrolled 4744 patients with HF and reduced ejection fraction (EF) who were receiving excellent guideline-directed treatment before the addition of dapagliflozin (a SGLT2 inhibitor) or placebo. The DAPA-HF trial clearly showed that dapagliflozin was superior to placebo at preventing CV deaths and HF events. The relative and absolute risk reductions in death and hospitalizations were consistent across subgroups including patients with and without diabetes; so, in consequence, dapagliflozin represents the first in a new class of drug for HF with reduced EF. The recently published Dapagliflozin Effects on Biomarkers, Symptoms, and Functional Status in Patients With Heart Failure With Reduced Ejection Fraction (DEFINE-HF) trial is also described in this review as well as the thought-to-be mechanisms of action of SGLT2 inhibitors beyond their known glucose-lowering effects. There is a vast, ambitious, and promising ongoing clinical investigation program with dapagliflozin and other SGLT2 inhibitors, which may result in changes to the therapeutic approach to HF in a relatively short time.